Exhaled breath temperature in children: reproducibility and influencing factors. (September 2014) - Vermeulen, S.; Barreto, M.; La Penna, F.; Prete, A.; Martella, S.; Biagiarelli, F.; Villa, M. P.
Abstract Objective: This study will investigate the reproducibility and influencing factors of exhaled breath temperature measured with the tidal breathing technique in asthmatic patients and healthy children. Methods: Exhaled breath temperature, fractional exhaled nitric oxide, and spirometry were assessed in 124 children (63 healthy and 61 asthmatic), aged 11.2 ± 2.5 year, M/F 73/51. A modified version of the American Thoracic Society questionnaire on the child's present and past respiratory history was obtained from parents. Parents were also asked to provide detailed information on their child's medication use during the previous 4 weeks. Ear temperature, ambient temperature, and relative-ambient humidity were also recorded. Results: Exhaled breath temperature measurements were highly reproducible; the second measurement was higher than the first measurement, consistent with a test–retest situation. In 13 subjects, between-session within-day reproducibility of exhaled breath temperature was still high. Exhaled breath temperature increased with age and relative-ambient humidity. Exhaled breath temperature was comparable in healthy and asthmatic children; when adjusted for potential confounders (i.e. ambient conditions and subject characteristics), thermal values of asthmatic patients exceeded those of the healthy children by 1.1 °C. Normalized exhaled breath temperature, by subtracting ambient temperature, was lower in asthmatic patients treated with inhaled corticosteroids than in those who were corticosteroid-naive. Conclusion: Measurements of exhaled breath temperature are highly reproducible, yet influenced by several factors. Corrected values, i.e. normalized exhaled breath temperature, could help us to assess the effect of therapy with inhaled corticosteroids. More studies are needed to improve the usefulness of the exhaled breath temperature measured with the tidal breathing technique in children.